RECONCILING MARRIAGE LAW AND POPULATION ADMINISTRATION LAW IN INDONESIA: THE LEGAL STATUS OF NIKAH SIRI AND THEIR FAMILIES - Andrizal; Bambang Hermanto; Muhammad Fauzan (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2026)
This article examines the normative misalignment between two Indonesian legal regimes that intersect over unregistered marriages (nikah siri): the marriage law regime, principally Law No. 1 of 1974 as amended by Law No. 16 of 2019, and the population administration regime under Law No. 24 of 2013 together with its implementing instruments, namely Minister of Home Affairs Regulation No. 9 of 2016 and Minister of Home Affairs Regulation No. 109 of 2019. The study asks two questions. First, how do these two regimes currently treat marriages that are religiously valid but not officially registered, and at which specific normative points do they diverge? Second, what targeted statutory and sub-statutory adjustments are required in order to align the marriage law regime with the documentary inclusivity already achieved within the population administration regime? The study employs a doctrinal legal method, supplemented by two key-informant interviews conducted with the Head of the Pasar Minggu Office of Religious Affairs and the Deputy for Coordination of Quality Improvement for Children, Women, and Youth at the Coordinating Ministry for Human Development and Culture. The interviews are used to illustrate institutional understandings of the two regimes rather than as a basis for empirical generalisation. The study finds that the two regimes operate on distinct regulatory objects: marriage law governs the formal validity and documentary proof of marriage, while population administration law governs the documentation of population events. The relationship between them is therefore best characterised as a partial normative misalignment rather than as a direct doctrinal conflict. On that basis, the article proposes a limited and operational adjustment, focused on three points: the textual separation of religious validity and administrative registration within Article 2 of Law No. 1/1974; the revision of Article 43 of Law No. 1/1974 and Article 100 of the Compilation of Islamic Law in line with Constitutional Court Decision No. 46/PUU-VIII/2010; and the inter-ministerial coordination of the SPTJM mechanism with the implementing regulations of the Marriage Law.